2022
DOI: 10.3390/ijerph19042113
|View full text |Cite
|
Sign up to set email alerts
|

Group Triple P Intervention Effects on Children and Parents: A Systematic Review and Meta-Analysis

Abstract: Supporting parents through the delivery of evidence-based parenting interventions (EBPI) is a way of promoting children’s rights, given the known benefits to child development and family wellbeing. Group Triple P (GTP) is an EBPI suitable for parents of children aged 2–12 years, who experience parenting difficulties, and/or child behavior problems. Even though GTP has been intensively studied, information lacks on the magnitude of its effects, considering the risk of bias within and across prior research. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Publication bias: not ascertained; Magnitude of effect similar across studies. Follow-up times in studies typically about 1 year – longer term follow up was rare Losel and Beelmann ( 2003 ) High Risk of bias: low due to RCTs; Precision: overall, small to moderate effect sizes observed; Consistent findings reported across studies; CBT Interventions directly related to outcome of interests; Publication bias: not ascertained; Magnitude of effect: Mostly medium; Dose response: N/A; Findings on confounder (age) increases GRADE Maughan et al, ( 2005 ) Moderate Risk of bias: Some risk of bias, including RCTs and non-RCT with variability in study quality; Precision: Overall moderate to large effect sizes observed, effect size varied by study quality; Interventions directly related to pop of interest; Publication bias: not ascertained; Mostly moderate magnitude of effect; Dose–response: N/A; Menting et al, ( 2013 ) Moderate Risk of bias: Low risk of bias due to mostly RCTs; Precision: Small effect sizes observed; Consistent findings reported across studies; IY Interventions directly related to outcome of interests; Publication bias: not ascertained; Magnitude of effect: Mostly weak; Dose response: N/A Mingebach et al, ( 2018 ) Moderate Risk of bias: overall risk of bias rated as satisfactory in the paper, consists of meta-analyses; Precision: Moderate effect sizes observed, with risk of bias analyses within paper suggesting robust results; Consistent findings reported across studies; Parenting-based interventions directly related to pop of interest; Publication bias: risk of bias analyses from funnel plots and fail-safe Ns suggest some but small publication bias; Magnitude of effect: Moderate; Dose–response: N/A Nogueira et al, ( 2022 ) Moderate Risk of bias: low risk of bias due to all RCTS, but some studies did not report randomization/blinding; Precision: small effect sizes (secondary outcomes) and moderate effect sizes (all GTP targeted outcomes); Interventions related to outcome; Publication bias: not ascertained; Magnitude of effect: mostly moderate; Dose response: N/A Nye ( 2019 ) High Risk of bias: low due to RCTs; Precision: Moderate effect sizes observed; Consistent findings reported across studies; Intervention directly related to outcome of interest; Publication bias: not ascertained due to small number of studies; Magnitude of effect: Medium; Dose response: N/A Parker et al, ( 2021a , 2021b ) …”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Publication bias: not ascertained; Magnitude of effect similar across studies. Follow-up times in studies typically about 1 year – longer term follow up was rare Losel and Beelmann ( 2003 ) High Risk of bias: low due to RCTs; Precision: overall, small to moderate effect sizes observed; Consistent findings reported across studies; CBT Interventions directly related to outcome of interests; Publication bias: not ascertained; Magnitude of effect: Mostly medium; Dose response: N/A; Findings on confounder (age) increases GRADE Maughan et al, ( 2005 ) Moderate Risk of bias: Some risk of bias, including RCTs and non-RCT with variability in study quality; Precision: Overall moderate to large effect sizes observed, effect size varied by study quality; Interventions directly related to pop of interest; Publication bias: not ascertained; Mostly moderate magnitude of effect; Dose–response: N/A; Menting et al, ( 2013 ) Moderate Risk of bias: Low risk of bias due to mostly RCTs; Precision: Small effect sizes observed; Consistent findings reported across studies; IY Interventions directly related to outcome of interests; Publication bias: not ascertained; Magnitude of effect: Mostly weak; Dose response: N/A Mingebach et al, ( 2018 ) Moderate Risk of bias: overall risk of bias rated as satisfactory in the paper, consists of meta-analyses; Precision: Moderate effect sizes observed, with risk of bias analyses within paper suggesting robust results; Consistent findings reported across studies; Parenting-based interventions directly related to pop of interest; Publication bias: risk of bias analyses from funnel plots and fail-safe Ns suggest some but small publication bias; Magnitude of effect: Moderate; Dose–response: N/A Nogueira et al, ( 2022 ) Moderate Risk of bias: low risk of bias due to all RCTS, but some studies did not report randomization/blinding; Precision: small effect sizes (secondary outcomes) and moderate effect sizes (all GTP targeted outcomes); Interventions related to outcome; Publication bias: not ascertained; Magnitude of effect: mostly moderate; Dose response: N/A Nye ( 2019 ) High Risk of bias: low due to RCTs; Precision: Moderate effect sizes observed; Consistent findings reported across studies; Intervention directly related to outcome of interest; Publication bias: not ascertained due to small number of studies; Magnitude of effect: Medium; Dose response: N/A Parker et al, ( 2021a , 2021b ) …”
Section: Methodsmentioning
confidence: 85%
“…We identified 22 meta-analyses, three systematic reviews, and one meta-meta-analysis, that evaluated behavioral-based parenting interventions. Commonly evaluated interventions included: Incredible Years (Forster et al, 2012 ; Furlong et al, 2012 ; Gardner et al, 2019a , 2019b ; Leijten et al, 2013 , 2016 , 2018 , 2020 ; Menting et al, 2013 ), Parent Child Interaction Therapy (Forster et al, 2012 ; Leijten et al, 2013 ), and Triple P (de Graaf et al, 2008 ; Forster et al, 2012 ; Leijten et al, 2013 , ; Nogueira et al, 2022 ; Tully & Hunt, 2016 ). More broad-based psychoeducational or behavioral skills-based programs were also evaluated (Cai et al, 2022 ; Dretzke et al, 2005 , 2009 ; Maughan et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…the 'Triple P' Positive Parenting Programme, Parent-Child Interaction Therapy and the Incredible Years) have achieved positive preventive impacts (National Academies of Sciences & Medicine, 2019). Furthermore, recent systematic reviews suggest that they can be delivered using technology-assisted/internet-based models (Florean, Dobrean, P as arelu, Georgescu, & Milea, 2020;Harrison et al, 2022;Nogueira, Can ario, Abreu-Lima, Teixeira, & Cruz, 2022), which may make them more accessible for parents and carers from a range of backgrounds and with a variety of needs.…”
Section: Interpersonal Interventionsmentioning
confidence: 99%
“…Gallart & Matthey, 2005). A meta‐analysis conducted by Sanders et al (2014) on 101 studies concluded that all Triple P intervention levels are effective in reducing parents' dysfunctional parenting practices, improving parental efficacy and satisfaction with their role and reducing children's behavioural issues, while another meta‐analysis conducted by Nogueira et al (2022) to evaluate the effects of Group Triple P in particular revealed that Group Triple P was effective in reducing behavioural problems in children, along with improving healthy parenting practices, sense of competence, relationship quality and mental wellbeing among parents. In light of this, Group Triple P was chosen as a suitable evidence‐based parenting support programme to be delivered for caregivers working in orphanages.…”
Section: Introductionmentioning
confidence: 99%